Whole-body-vibration-induced increase in leg muscle activity during different squat exercises - Roelants, M.; Verschueren, S. M. P.; Delecluse, C.; Levin, O.; Stijnen, V. (The Journal of Strength and Conditioning Research, 2006)
This study analyzed leg muscle activity during whole-body vibration (WBV) training. Subjects performed standard unloaded isometric exercises on a vibrating platform (Power Plate): high squat (HS), low squat (LS), and 1-legged squat (OL). Muscle activity of the rectus femoris, vastus lateralis, vastus medialis, and gastrocnemius was recorded in 15 men (age 21.2 ± 0.8 years) through use of surface electromyography (EMG). The exercises were performed in 2 conditions: with WBV and without (control [CO]) a vibratory stimulus of 35 Hz. Muscle activation during WBV was compared with CO and with muscle activation during isolated maximal voluntary contractions (MVCs). Whole-body vibration resulted in a significantly higher (p < 0.05) EMG root-mean-square compared with CO in all muscle groups and all exercises (between +39.9 ± 17.5% and +360.6 ± 57.5%). The increase in muscle activity caused by WBV was significantly higher (p < 0.05) in OL compared with HS and LS. In conclusion, WBV resulted in an increased activation of the leg muscles. During WBV, leg muscle activity varied between 12.6 and 82.4% of MVC values.